2015
DOI: 10.1186/s40557-015-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of lead exposure

Abstract: Lead, which is widely used in industry, is a common element found in low concentrations in the Earth’s crust. Implementations to reduce environmental lead concentrations have resulted in a considerable reduction of lead levels in the environment (air) and a sustained reduction in the blood lead levels of the average citizen. However, people are still being exposed to lead through a variety of routes in everyday commodities.Lead causes health problems such as toxicity of the liver, kidneys, hematopoietic system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 58 publications
0
82
0
2
Order By: Relevance
“…Do niekorzystnych efektów, jakie wywiera ten metal, można zaliczyć uszkodzenia układów: nerwowego, krwionośnego, krwiotwórczego i rozrodczego, a także nerek oraz wątroby [6,7]. Podczas zatrucia ołowiem może dojść do uszkodzenia istoty białej mózgu.…”
Section: Wyniki Przegląduunclassified
See 1 more Smart Citation
“…Do niekorzystnych efektów, jakie wywiera ten metal, można zaliczyć uszkodzenia układów: nerwowego, krwionośnego, krwiotwórczego i rozrodczego, a także nerek oraz wątroby [6,7]. Podczas zatrucia ołowiem może dojść do uszkodzenia istoty białej mózgu.…”
Section: Wyniki Przegląduunclassified
“…Zmiany te mogą następnie wywoły-wać zaburzenia w ekspresji genów, hamowanie procesów naprawy DNA i stymulację syntezy DNA [9]. Mię-dzynarodowa Agencja Badań nad Rakiem (International Agency for Research on Cancer -IARC) klasyfikuje nieorganiczne związki ołowiu jako prawdopodobnie rakotwórcze dla ludzi (grupa 2A) [6].…”
Section: Wyniki Przegląduunclassified
“…Figure 7 represents the finding that 51% literate laypersons and 78% medical professionals agreed that other nutrients like Vitamin B1 and Vitamin D also help to excrete lead from brain and bone respectively, while only 7% illiterate laypersons showed positive thinking about this. Literature evaluation also showed that vitamin D can play a role in decreasing the quantity of lead stored in the bone, and B1 (thiamine), specifically increases excretion of lead from the brain [17]. About the role of herbal remedies to overcome lead poisoning survey studies and Figure 8 showed that 25% literate laypersons and 35% medical professionals have not any idea but 20% laypersons and 45% medical professionals said that herbal remedies like turmeric, Glycerrhiza glabra and fennel seeds all are helpful in reducing lead poisoning while 47% illiterate laypersons said that turmeric is helpful in reducing lead poisoning.…”
Section: Figure 5: Sources Through Which Lead Poisoning Occurs In Unbmentioning
confidence: 99%
“…Vitamin D and Vitamin B9 (Folate) act by increasing lead absorption in the body which leads to decreased concentration of lead stores in body. Vitamin B1 (thiamine) increases lead excretion from brain [17]. In pharmacological treatment, chelation therapy can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to lead at 10 µg/dl may already inhibit ALAD, causing accumulation of aminolevulinic acid, so resulting in failure of heme synthesis that carries the risk of anemia. (6) Cases of anemia are usually also accompanied by an increase in reticulocyte count. A low reticulocyte count indicates aplasia or disorders of the bone marrow.…”
Section: Introductionmentioning
confidence: 99%